77.3k views
3 votes
(2+√-4) (3 +5i)(-4-i)

User AishApp
by
5.3k points

2 Answers

6 votes

Answer:


32-60i

Explanation:

Given expression:


(2+√(-4))(3 +5i)(-4-i)


\textsf{Rewrite $√(-4)$ as $√(4 \cdot -1)$}:


\implies (2+√(4 \cdot -1))(3 +5i)(-4-i)


\textsf{Apply radical rule} \quad √(ab)=√(a)√(b):


\implies (2+√(4)√(-1))(3 +5i)(-4-i)


\implies (2+2√(-1))(3 +5i)(-4-i)


\textsf{Apply imaginary number rule} \quad √(-1)=i:


\implies (2+2i)(3 +5i)(-4-i)

Multiply:


\implies (6+16i+10i^2)(-4-i)


\implies -24-6i-64i-16i^2-40i^2-10i^3


\implies -24-70i-56i^2-10i^3


\textsf{Apply imaginary number rule} \quad i^2=-1:


\implies -24-70i-56(-1)-10(-1)i

Simplify:


\implies -24-70i+56+10i


\implies 32-60i

User Thepocketwade
by
5.8k points
4 votes

Answer:


  • 32-60i

----------------------------------------

Simplify the expression in below steps:


  • (2+√(-4) ) (3 +5i)(-4-i)=

  • (2+√(-1*4) ) (3 +5i)(-4-i)=

  • (2+2i ) (3 +5i)(-4-i)=

  • 2(1+i ) (3 +5i)(-4-i)=

  • 2(1+i ) (3(-4) -3i+5i(-4)-5i*i)=

  • 2(1+i ) (-12 -3i-20i-5(-1))=

  • 2(1+i ) (-12 -23i+5)=

  • 2(1+i ) (-7 -23i)=

  • 2(-7 -23i -7i-23i*i)=

  • 2(-7 -30i +23)=

  • 2(16 -30i)=

  • 32-60i

User Rostislav V
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.